2021
DOI: 10.1049/cit2.12052
|View full text |Cite
|
Sign up to set email alerts
|

Stock values predictions using deep learning based hybrid models

Abstract: Predicting the correct values of stock prices in fast fluctuating high-frequency financial data is always a challenging task. A deep learning-based model for live predictions of stock values is aimed to be developed here. The authors' have proposed two models for different applications. The first one is based on Fast Recurrent Neural Networks (Fast RNNs). This model is used for stock price predictions for the first time in this work. The second model is a hybrid deep learning model developed by utilising the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…In addition, various researchers have worked on different ML techniques to classify breast cancer types. It is found that the existing models suffer from the gradient vanishing [ 22 24 ], overfitting [ 25 , 26 ], and data leakage [ 27 , 28 ] kind of problems. Even development of generalized model [34,35] is still defined as an ill-posed problem.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, various researchers have worked on different ML techniques to classify breast cancer types. It is found that the existing models suffer from the gradient vanishing [ 22 24 ], overfitting [ 25 , 26 ], and data leakage [ 27 , 28 ] kind of problems. Even development of generalized model [34,35] is still defined as an ill-posed problem.…”
Section: Related Workmentioning
confidence: 99%
“…The pooling layer takes samples from the feature maps and extracts the most important features in each feature map to pass to the fully connected layer. Finally, the fully connected layer obtains the final classification result of the headlines using the SoftMax function [12] and outputs the event type of the headlines. The daily news about a particular stock is counted by the CNN news classifier.…”
Section: Classification Of News Events Based On Cnn Modelmentioning
confidence: 99%
“…The empirical results of news event classification are shown in Table 5. To verify the performance of the CNN-based news event classifier, it was compared with the SVM and maximum entropy methods [9][10][11][12] for news event classification. SVM is widely investigated and applied for modeling, classification, and data-driven error detection as it has been shown to be powerful and generalizable, while maximum entropy is a linear logit model with proven classification capabilities.…”
Section: News Event Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The former is called univariate time series forecasting; the latter is called multivariate time series forecasting. For example, economists utilized the historical data of stock prices to forecast stock prices or trends [ 5 ], medical scientists made use of the biological time data to predict diseases [ 6 ], transportation departments explored the historical data of traffic flow to predict congestion [ 7 ], and environmentalists employed atmospheric timing data to estimate environmental climate changes [ 8 ], etc. Nevertheless, time series data not only contains abundant information but also appears to some complex characteristics such as high dimension, nonlinear, fluctuation, and spatiotemporal dependence, which make accurate time series data prediction become a challenging study hotspot [ 9 ].…”
Section: Introductionmentioning
confidence: 99%